Description of five new Aname L. Koch, 1873 (Araneae, Anamidae) species collected on Bush Blitz expeditions - Wilson, Jeremy Dean; Rix, Michael Gordon; Harvey, Mark Stephen (European Journal of Taxonomy, 2023)
Aname L. Koch, 1873 is an incredibly diverse genus of mygalomorph spiders endemic to Australia, occurring from coast to coast in tropical, semi-arid and arid bioregions. They are relatively gracile mygalomorph spiders that build open burrows, sometimes with a secondary entrance that functions as an escape chute. The genus currently contains 48 species, but the true diversity is likely to be closer to 200 species. Here we describe five new species (A. ningaloo sp. nov., A. salina sp. nov., A. tatarnici sp. nov., A. tenuipes sp. nov. and A. wongalara sp. nov.), primarily based on specimens collected on Bush Blitz expeditions in Western Australia (Cape Range, 2019), South Australia (Great Victoria Desert, 2017) and the Northern Territory (Wongalara, 2012). We complement these descriptions with a molecular phylogenetic analysis to place all new species into an existing phylogenetic framework.